Protection of tomato plants against Fusarium oxysporum f. sp. lycopersici induced by chitosan - Carmona, Sandra L.; Villarreal-Navarrete, Andrea; Burbano-David, Diana; Gómez-Marroquín, Magda; Torres-Rojas, Esperanza; Soto-Suárez, Mauricio (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2021)
Physiological processes of plants infected by vascular pathogens are mainly affected by vascular bundle obstruction, decreasing the absorption of water and nutrients and gas exchange by stomatal closure, and inducing oxidative cascades and PSII alterations. Chitosan, a derivative of chitin present in the cell wall of some organisms including fungi, induces plant defense responses, activating systemic resistance. In this study, three chitosan molecules (low, medium and high molecular weight) at different concentrations (0.5, 1, 1.5, 2, 2.5 and 3 mg mL-1) were assessed by in vitro tests against Fusarium oxysporum f. sp. lycopersici (Fol). Concentrations higher than 1 mg mL-1 were found to inhibit significantly the mycelial growth of Fol, with 95.8% of inhibition using chitosan with high molecular weight (3 mg mL-1). For in planta assays, chitosan treatment (low molecular weight 2.5 mg mL-1) showed significantly lower incidence and severity of wilting disease symptoms, 70 and 91%, respectively, compared to healthy plants used as a negative control. The effect of chitosan on the physiological and molecular responses of tomato plants infected with Fol was studied, evaluating the maximum potential quantum efficiency of PSII photochemistry (Fv/Fm), photochemical efficiency of PSII (Y(II)), stomatal conductance (gs), relative water content (RWC), proline content, photosynthetic pigments, dry mass, and differential gene expression (PAL, LOXA, ERF1, and PR1) of defense markers. A reduction of 70% in the incidence and 91% in the severity of the disease was achieved in plants treated with chitosan, mitigating the damage caused by Fol on Fv/Fm, Y(II), and chlorophyll contents by 23, 36, and 47%, respectively. Less impact was observed on gs, RWC, and dry mass (55, 11, and 26%, respectively). Chitosan-treated and Fol-infected plants over-expressed PR1a gene suggesting a priming-associated response. These results demonstrate the high potential of chitosan to protect tomato plants against Fol by regulating physiological and molecular responses in tomato plants.